THE INFLUENCE OF POPULAR MEDIA ON YOUNG INDONESIAN WOMAN WEARING HIJAB - Simorangkir, Deborah (Journal of Business And Entrepreneurship, 2024)
Indonesia has been experiencing a rise in Islamic conservatism, and with that, a rapid increase in the number of women wearing the hijab. There has also been an increase in the production and consumption of Islamic content in popular media targeted at young Indonesians. This study analyzes how popular media influences girls in their decision to wear hijab. Findings from in-depth interviews with 10 university hijab-wearing students show that though they decided to wear the hijab because they believe it to be proper Islamic behavior, still, family, friends, and celebrities have also been influential in their decision. Indonesian popular media portray women in hijab in a positive light. All respondents agreed that throughout their experience wearing the hijab, popular media has served them in various ways, including style inspiration. Based on Stuart Hall’s Reception Theory, most respondents have taken the Dominant-Hegemonic position when consuming media messages pertaining the hijab. A small minority, however, took the Negotiated position because they feel that the media should portray women who wear the hijab just as any other woman.